Pencarian Jalur Terpendek Jakarta ke Jawa Barat Berbasis Algoritma Genetika - Firyal Wishal Nabili; Eva Yulia Puspaningrum; Afina Lina Nurlaili (Ikatan Ahli Informatika Indonesia, 2025)
The Travelling Salesman Problem (TSP) is a well-known combinatorial optimization problem aimed at finding the shortest route that visits each location exactly once and returns to the starting point. This study aims to determine the shortest travel route from Jakarta to all cities in West Java Province using a Genetic Algorithm (GA). Distance data between cities were obtained from the Central Bureau of Statistics (BPS) of Bekasi Regency and used to construct a distance matrix for distance calculation. The optimization process employed a population size of 100 individuals, a crossover rate of 0.7, a mutation rate of 0.05, and 500 generations. The algorithm used Roulette Wheel Selection for parent selection, PMX (Partially Mapped Crossover) for crossover, swap mutation for mutation, and elitism to preserve the best individuals across generations. Experimental results show that the initial route distance of 2918 km was reduced to 1314 km at generation 110 and remained stable until generation 500. The optimal route found was: Jakarta ? Bekasi ? Karawang ? Tangerang ? Serang ? Pandeglang ? Lebak ? Bogor ? Sukabumi ? Cianjur ? Subang ? Indramayu ? Kuningan ? Cirebon ? Tasikmalaya ? Ciamis ? Majalengka ? Sumedang ? Garut ? Bandung ? Purwakarta ? Jakarta. These results demonstrate that the Genetic Algorithm effectively provides optimal route solutions with fast convergence and high efficiency in solving the TSP.